Pendekatan Tafsir Inklusif dalam Menjawab Persoalan Kesetaraan Gender di Madura: Sebuah Pendekatan Inklusif - Bakir, Moh; Kahar, Abd. (Universitas Islam Negeri Madura, 2025)
Traditional gender roles persistently position men as primary breadwinners and decision-makers, while relegating women to domestic and caregiving responsibilities, thereby reinforcing systemic gender inequality and restricting women’s access to equitable education and employment opportunities. This study employs an inclusive hermeneutical approach to Qur’anic exegesis—integrating textual analysis, contextual considerations, and principles of openness—to reconceptualize gender dynamics in Madurese society, where patriarchal interpretations remain entrenched. Through descriptive-analytical methodology, the research demonstrates that an inclusive interpretive framework, responsive to contemporary sociocultural conditions, offers a transformative understanding of gender roles by harmonizing religious hermeneutics with local realities. The findings highlight the approach’s efficacy in advancing more equitable and contextually relevant solutions, thereby fostering a more just and humane gender paradigm in Madura.